2004
DOI: 10.1161/01.cir.0000145610.64014.e4
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Multicenter Trial of Empirical Antitachycardia Pacing Versus Shocks for Spontaneous Rapid Ventricular Tachycardia in Patients With Implantable Cardioverter-Defibrillators

Abstract: Background-Successful antitachycardia pacing (ATP) terminates ventricular tachycardia (VT) up to 250 bpm without the need for painful shocks in implantable cardioverter-defibrillator (ICD) patients. Fast VT (FVT) Ͼ200 bpm is often treated by shock because of safety concerns, however. This prospective, randomized, multicenter trial compares the safety and utility of empirical ATP with shocks for FVT in a broad ICD population. Methods and Results-We randomized 634 ICD patients to 2 arms-standardized empirical AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
482
4
13

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 693 publications
(519 citation statements)
references
References 21 publications
20
482
4
13
Order By: Relevance
“…Until recently, default device programming used short-duration "detection" criteria that varied by manufacturer and a tachycardia rate of approximately 2.8 to 5 seconds before either ATP or charging (including detection time plus duration or number of intervals) [82,93]. With increased awareness of the potential harm from inappropriate shocks and the realization from stored pacemaker EGMs that even long episodes of VT can self-terminate, a strategy of prolonged detection settings has been explored.…”
Section: Duration Criteria For the Detection Of Ventricular Arrhythmiamentioning
confidence: 99%
See 4 more Smart Citations
“…Until recently, default device programming used short-duration "detection" criteria that varied by manufacturer and a tachycardia rate of approximately 2.8 to 5 seconds before either ATP or charging (including detection time plus duration or number of intervals) [82,93]. With increased awareness of the potential harm from inappropriate shocks and the realization from stored pacemaker EGMs that even long episodes of VT can self-terminate, a strategy of prolonged detection settings has been explored.…”
Section: Duration Criteria For the Detection Of Ventricular Arrhythmiamentioning
confidence: 99%
“…This programming might improve survival [126]. Indeed, several studies have shown that ATP is effective at terminating slow and fast VT with exceedingly low rates of adverse events like syncope [93,135,[161][162][163][164][165]. The initial bias of the ICD community was to reserve ATP therapy for those patients in whom the therapy was demonstrated to be effective, usually during an electrophysiologic study.…”
Section: Tachycardia Therapy Programmingmentioning
confidence: 99%
See 3 more Smart Citations